2018
DOI: 10.18805/ijare.a-4977
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant geometry on growth, yield and quality of different varieties of fenugreek (Trigonella foenum-graecum L.)

Abstract: An experiment entitled effect of plant geometry on growth, yield and quality of different varieties of fenugreek was carried out during rabi season of 2016-17at College of Horticulture, Mandsaur (M.P.) with 12 treatment combinations, comprising three plant geometry 20 cm x 15cm, 30 cm x 10cm and 30 cm x 15 cm with four varieties of fenugreek i.e. AFg-1, AFg-2, AFg-3 and AFg-4. These treatments were replicated four times in split spot design and analyzed. Treatment with plant geometry 20 cm ×15 cm recorded sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
4
4
0
Order By: Relevance
“…The reason for higher value of fresh weight due to plant have capacity to harvested maximum sunlight and synthesize photosynthates. These findings were agreement with Latye et al (2016) [9] and Sharanya et al (2018) [15] in fenugreek. The present study revealed that, the maximum chlorophyll content SPAD value (57.29, 67.42, 78.56 and 52.94) was recorded in V10 PEB at 30, 60, 90 DAS and at harvest respectively.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The reason for higher value of fresh weight due to plant have capacity to harvested maximum sunlight and synthesize photosynthates. These findings were agreement with Latye et al (2016) [9] and Sharanya et al (2018) [15] in fenugreek. The present study revealed that, the maximum chlorophyll content SPAD value (57.29, 67.42, 78.56 and 52.94) was recorded in V10 PEB at 30, 60, 90 DAS and at harvest respectively.…”
Section: Resultssupporting
confidence: 93%
“…The significant difference in the chlorophyll content SPAD value may be due to genetic character of the variety. These results obtained are accordance with the findings of Kuri et al (2015) [8] in coriander, Gurjar et al (2016) [5] , Hosamath et al (2017) [6] , Sharanya et al (2018) [15] in fenugreek. The significant variations were observed in seed yield.…”
Section: Resultssupporting
confidence: 91%
“…The result showed that treatment T4 (Rhizobium + NAA) gave the minimum (4.00) days required for seed germination and it was found 46 significantly superior as compared to all other treatments, while the maximum days required for seed germination (6.67) was recorded in treatment T1 (Control). The results are in confirmation with the results achieved by Meena et al [9] and Sharanya et al [10].…”
Section: Growth Parameterssupporting
confidence: 92%
“…However, the treatment T1 (Control) gave the minimum protein content, ascorbic acid and chlorophyll content in fenugreek. Similar results for most of the characters were also reported by Singh et al [11], Yugandhar et al [15], Talab et al [18], Yugandhar et al [16],Govind et al [19] and Sharanya et al [10,20].…”
Section: Quality Parameterssupporting
confidence: 86%
“…Similarly, Parameshwari et al (2003) was also recorded the higher seed yield in 120 x 30 cm spacing was due to optimum plant population per unit area which could not be compensated by increase in yield attributes like plant height number of branches, number of pods and seed per plant under wider spacing (150 x 30 cm). Similarly Sharanya et al (2018) higher yield and ascribed to the better growth of plants under broader spacing and it exhibited better vegetative growth due to less plant population density and competition which resulted in more horizontal growth and plant canopy area compared to those under narrow spacing. So the branch bearing capacity increased.…”
Section: Resultsmentioning
confidence: 99%